Investigations on Quasi-Steady Characteristics for an Airfoil Oscillating at Low Reduced Frequencies - Deepakkumar M. Sharma; Kamal Poddar (International Journal of Aerospace Engineering)
Wind tunnel experiments were conducted on NACA-0015 airfoil model to investigate the effect of the reduced frequency (κ=0.0001 to 0.5) and that Reynolds number (Re=0.2E06 to 0.7E06) on the aerodynamic characteristics and hysteresis behavior associated with the oscillating motion of the airfoil. Pressure measurements were conducted on the midspan of the airfoil for quantitative results. Although dynamic stall study has been conducted to greater extent of reduced frequencies, for current work, emphasis is made on investigating the low reduced frequency regimes up to which the steady conditions prevail under dynamic mode of operation. In present investigations of oscillating sinusoidal α=10∘+15∘sin(ωt) motion, the airfoil was allowed to execute oscillating motion from static to almost steady (quasi-steady) conditions with the incremental increase in the reduced frequency. The limiting conditions of κ and Re for quasi-steady state are carefully extracted and analyzed. Static and quasi-steady conditions are critically assessed in context of the existence of laminar separation bubble within the opted Re regime. The flow separation was found to be trailing edge flow separation with existence of LSB upstream towards the leading edge with no evidence of unsteady flow reversals. Normal force defect and pitch damping factor are estimated for varied range of Re and κ within the quasi-steady conditions. Re effect is dominant at steady and quasi-steady regimes while the effect of reduced frequency is negligible in this domain. Minor hysteresis effect associated with the stalling and reattachment point is due to existence of weak stall flutter which is further restrained by the oscillatory motion of the airfoil. Laminar separation bubble traced during steady condition is conserved in quasi-steady domain as well.